Using the Factor Tree Strategy to Overcome Learning Difficulties for Junior High School Students in Helping to Solve Square Roots - Ade Mahmud Eka Sabani (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
The problem in the research is the difficulty of students in solving problems of the square root of integers (perfect squares) and cube roots of integers (cubic numbers) using an algorithm strategy better known as porogapit. This problem was obtained when giving tutoring to several junior high school students in Purworejo. The algorithm or porogapit strategy was taught when I was in elementary school. Still, as the learning model developed, the strategy could have been more efficient and took a long time. Only a few students remembered the strategy. Today's students even use a trial-and-error strategy: try the same multiplication number one by one or raise the numbers sequentially until the number in question. The trial and error strategy solved only the square root of integers (perfect square). In contrast, when there was a problem with the square root of imperfect integers (irrational squares), they still had difficulty solving it. The results showed that it was easier for students to master the factor tree strategy in solving square root problems than the algorithmic and trial-and-error strategies. Furthermore, the factor tree strategy can assist students in solving the square root problem, both the square root of perfect integers and the square root of imperfect numbers (irrational squares). Keywords: Students Learning Difficulties, Square Root Solutions.